CRITICAL REVIEW ON TEACHER’S BELIEF ABOUT TEACHING READING STRATEGIES AND THEIR CLASSROOM PRACTICES: A CASE STUDY OF VIET BA HIGH SCHOOL - Agnes Widyaningrum (Dinamika Bahasa dan Budaya, 2012)
There are four English skills that should be mastered by students, namely listening, speaking, reading and writing. Among those four English skills, reading is mainly discussed in every field. It means that reading becomes a universal habit inspite of the language used in reading text. As one of English skills, reading is admitted as an essential skill for English as a Second or Foreign Language (ESL/EFL). Some teachers believe that reading is an important skill to master because if students are able to master reading, as readers they will make progress and attain greater development in their academic atmosphere. Reading involves brain activity as the information that is read will be stored in the brain. By strengthening this skill, it is possible that students will gain greater knowledge in their academic life. Moreover, English is used in many areas outside of academic like in politics, economics, technology, tourism, culture and science. Therefore English is not only a means but also a key to access and asses many sophisticated achievement yield by many countries in the world.   Key words: ESL/EFL, reading skill, teacher’s belief